Gender characteristics of retinal parameters in patients with uncomplicated hypertension - A. V. Barsukov; K. A. Shcherbakova; M. A. Burnasheva; D. S. Maltsev; A. N. Kulikov; A. E. Korovin; M. V. Yasenovets; A. V. Gordienko (Кардиоваскулярная терапия и профилактика)
Aim. To establish gender specificities of retinal arteriolar and venular diameters, foveal avascular zone (FAZ) area, subfoveal choroid thickness (SCT), and to determine their association with cardiovascular risk and prognosis in patients with uncomplicated hypertension (HTN).Material and methods. The study included 70 patients (56 males and 14 females) aged 45-59 years with stage I or II HTN. There were following  exclusion  criteria:  diabetes,  liver  failure,  clinically  relevant  ophthalmic pathology. We assessed routine hemodynamic parameters, biochemical profile, serum N-terminal procollagen-III peptide, urinary albumin-creatinine ratio, 24-hour urinary albumin excretion, retinal parameters. All patients underwent electrocardiography and echocardiography. Ten-year risk of fatal cardiovascular disease (SCORE) was estimated. Based on scanning laser ophthalmoscopy, central   retinal   arterial   (CRAE)   and   venous   (CRVE)   equivalents, arteriovenous ratio (AVR) were calculated. Using optical coherence tomography angiography, we determined FAZ area and SCT. Data processing was performed using StatSoft Statistica 10.Results. Hypertensive women were characterized by significantly larger FAZ area (p<0,001), CRVE  (p=0,005), CRAE (p=0,012)  compared with men. SCT values (p>0,05) were comparable. CRVE was associated with Cornell voltage product (r=0,3) in the male group. In women, age was negatively correlated with SCT (r=-0,54); SCORE value was inversely associated with SCT (r=-0,56), AVR (r=-0,53), CRAE (r=-0,3).Conclusion. In patients with uncomplicated HTN, the gender specificities of retina are manifested by a relative decrease of arteriolar diameters in males and a relative increase of venular diameters and FAZ in females. SCT decreases most clearly with age among hypertensive women. Men are characterized by a direct association of retinal venular diameters with a quantitative electrocardiographic marker of left ventricular hypertrophy. In women, there are an inverse association of SCT and arteriolar diameters with a ten-year risk of fatal cardiovascular  disease.